Pengaruh Brand Image dan Brand Ambassador Terhadap Keputusan Pembelian Pada Aplikasi Bukalapak - Martadiyani, Fany; Sarah, Siti (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This research endeavours to examine the impact of Brand Image and Brand Ambassador on Purchasing Decisions within the Bukalapak Application, employing quantitative research methodologies alongside verification and descriptive analytical approaches. The primary data were gathered through pre-surveys, questionnaires, document compilation, and interviews, specifically targeting consumers who had conducted transactions on the Bukalapak Application. The study's sample was selected using a non-probabilistic sampling method, namely the assessment sample technique, resulting in a population and research sample of 100 users who had engaged in transactions on the Bukalapak Application. Regression analysis findings revealed that Brand Image and Brand Ambassador significantly affected Purchasing Decisions, whilst the coefficient of determination yielded a value of 0.950 or 95%. This indicates that the Brand Image and Brand Ambassador variables collectively influenced Purchasing Decisions by 95%, with the remaining 5% attributed to other factors.